Population, Development, and the Environment
XXXVI, 440 p. 110 illus.
Keywords: This book takes the reader into some of the most intransigent social, economic, and political issues that impact achieving sustainable development in Asia and the Pacific. Through meticulous analysis of the integrated relationships between population, development, and the environment, the chapters in this volume investigate the impacts of hydropower development on fragile ecosystems; mining, landslides and environmental degradation; deforestation; water and food security; rural-urban migration, poverty alleviation, civil society and community empowerment; and how disaster recovery requires multi-scalar and multi-disciplinary approaches that take into account governance, culture, and leadership. Legal frameworks may be legislated, but are often rarely implemented. The book will be valuable to students of sustainability, population and development, and governmental policy advising sectors as well as the NGO and humanitarian sectors. The distinctive characteristic of this book is that it encapsulates an integrated, multi-disciplinary focus which brings to the discussion both robust empirical research and challenging policy applications in the investigation of how the sustainable development goals may be achieved in Asia and the Pacific. Helen James researches Asian disasters, Risk, Resilience and Reconstruction, civil society, governance, health, education, poverty alleviation and sustainable development in Southeast Asia with special attention to the political anthropology of religion, non-violence and state/civil society relations, health and social inclusion/exclusion, international development, gender and health, citizenship, human rights and human security, interfaith dialogue and transnational history.